Repetition of Prediabetes Enhances the Risk of Developing Diabetes - Yoshihiro Numata; Toshihide Ohya; Yasuhiko Nitta; Yumiko Yoshinaka; Azusa Shogakiuchi; Akihiro Toyota (Journal of Diabetes Research)
We attempted to clarify the severity of the risk of diabetes mellitus (DM) in the individuals who repeatedly fulfill the criteria for prediabetes in both fasting plasma glucose (FPG) and hemoglobin A1c (HbA1c). The subjects were 2347 individuals who underwent annual health checkup at our hospital. They were classified as normal glucose tolerance or prediabetes as their yearly status of glucose tolerance for three years; furthermore, the individuals classified as prediabetes were subclassified into 3 groups. Among them, we focused the individuals who fulfilled the criteria for prediabetes in both FPG and HbA1c, and this group was named as PD3. Similarly, all subjects were categorized into 4 groups by the frequency of the status of PD3 during three years. Moreover, all subjects were categorized into 8 patterns when PD3 status was positive. Then, we surveyed the development of diabetes for 5 years, and the incidence rates (IRs) and the age- and sex-adjusted odds ratios (ORs) were obtained. A total of 188 subjects developed diabetes. The individuals in the group of PD3 showed the highest IR of DM (33.6%). The values of ORs were 11.5, 20.0, and 63.5 when the frequencies of PD3 were one, two, and three, respectively. In the group whose frequency of PD3 was two, the individuals who had repeated the status of PD3 twice then moved to the status other than PD3 showed smaller risk of DM than the others in the same group. In conclusion, individuals who fulfill the criteria for prediabetes in both FPG and HbA1c were at a high risk of developing DM, and the risk was enhanced by repeating this status. On the other hand, changing the status from PD3 to others might reduce the risk of DM.